Performance modelling of textile solar cell developed by carbon fabric/polypyrrole flexible counter electrode. Issue 8 (14th September 2022) - Saberi Motlagh, Mahmoud; Mottaghitalab, Vahid; Rismanchi, Asghar; Rafieepoor Chirani, Mahboobeh; Hasanzadeh, Mahdi
ABSTRACT: In this research, the carbon fabric (CF) is coated with polypyrrole (PPy) monomer via electropolymerisation and used as a flexible counter electrode. The polypyrrole coated carbon fabric (PPy-CF) counter electrode surface shows a homogenous coating of the polypyrrole film. The PPy-CF counter electrode exhibits appropriate electrical conductivity and suitable electron/hole charge transfer in the electrode/electrolyte interface in the electrical double layer (EDL) and adequate redox electrocatalytic activity. Also, dye-sensitised solar cell (DSSC) based on the PPy-CF counter electrode achieved 3.86% of power conversion efficiency (PCE). Furthermore, drift-diffusion modelling, based on the homogenisation theory has been established to appraise the photovoltaic performance. This study extends novel visions towards applying electro-conductive fabric based on polypyrrole for the optoelectronic textile devices. GRAPHICAL ABSTRACT: UF0001